2013
DOI: 10.1071/sr12338
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble pedotransfer functions to derive hydraulic properties for New Zealand soils

Abstract: Modelling water and solute transport through soil requires the characterisation of the soil hydraulic functions; however, determining these functions based on measurements is time-consuming and costly. Pedotransfer functions (PTFs), which make use of easily measurable soil properties to predict the hydraulic functions, have been proposed as an alternative to measurements. The better known and more widely used PTFs were developed in the USA or Europe, where large datasets exist. No specific PTFs have been publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…Cichota et al (2013) also reported that PTFs developed in Europe and the USA were not applicable to New Zealand. The reasons why these PTFs are not directly applicable to New Zealand require further investigation.…”
Section: Optimal Tortuosity Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…Cichota et al (2013) also reported that PTFs developed in Europe and the USA were not applicable to New Zealand. The reasons why these PTFs are not directly applicable to New Zealand require further investigation.…”
Section: Optimal Tortuosity Parametersmentioning
confidence: 99%
“…However, the predictions of K s were found to be too coarse for application to the wide range of soils within Smap. Therefore, Cichota et al (2013) tested published statistical PTFs developed in Europe and the USA to predict θ (h) and K(θ ) for a range of New Zealand soils. They combined the best two or three PTFs to construct ensemble PTFs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar functions were developed and tested later by Minasny et al (1999), Tomasella et al (2000), and Børgesen et al (2008) for soils from New Zealand, Brazil, and Denmark, respectively. Further developments beyond the classical regression analysis include techniques like artificial neural networks (Schaap and Leij, 1998a, 1998b; Minasny and McBratney, 2002; Merdun et al, 2006; Baker and Ellison, 2008; Campos de Oliveira et al, 2017; D’Emilio et al, 2018), pattern recognition based methods including support vector machine (Nemes et al, 2006; Lamorski et al, 2008; Khlosi et al, 2016), Gaussian process regression (Kotlar et al, 2019b), and the ensemble approach (Baker and Ellison, 2008; Cichota et al, 2013; Liao et al, 2015), all of which contributed to the improvement of PTF performance in predicting soil hydraulic properties.…”
mentioning
confidence: 99%